BADUI HOUSE AS AN IDEA SOURCE FOR CREATING CHILDREN'S BATIK MOTIFS - Agustin, Lisa Tri; Purnomo, Muhammad Arif Jati (ISI Press Institut Seni Indonesia Surakarta, 2023)
Badui (Bedouin) tribe is one of the ethnic groups that continues to exist and thrive today, including the traditional house-building method. Accordingly, the Badui traditional house is transformed into a batik motif for the children's casual dress to maintain continuity. This creation seeks to design and implement the traditional Badui house batik motif in casual clothing for 10-year-old girls. Exploration, design, and embodiment were the means of creating works. The process of creating works startedwithexploring motifs, clothing, material, and technique, followed by motifs and children's casual clothing designs. This work utilizedthe written batik technique;colet-tutup-celupcoloring;Remasol, Naptol, and Indigosol dyes; Japanese cotton and Primissima; and bright colors as embodiment techniques. Implementing batik motifs (ImahSawarna,ImahNgahiji,ImahSalonjor,ImahKahuripan) to children's casual clothing resulted in 4 pieces of clothing, namely: Inleum, Makaul, Galis, and Bageur.